Distribution of Force in the Medial Collateral Ligament Complex During Simulated Clinical Tests of Knee Stability. (May 2016) - Schafer, Kevin A.; Tucker, Scott; Griffith, Timothy; Sheikh, Saad; Wickiewicz, Thomas L.; Nawabi, Danyal H.; Imhauser, Carl W.; Pearle, Andrew D.
Background: Pivot-shift injury commonly results in combined anterior cruciate ligament (ACL)/medial collateral ligament (MCL) injury, yet the contribution of the components of the MCL complex to restraining multiplanar rotatory loads forming critical subcomponents of the pivot shift is not well understood. Purpose: To quantify the role of the MCL complex in restraining multiplanar rotatory loads. Study Design: Controlled laboratory study. Methods: A robotic manipulator was used to apply combined valgus and internal rotation torques in a simplified model of the pivot-shift examination in 12 cadaveric knees (49 ± 11 years). Tibiofemoral kinematics were recorded with the ACL intact. Loads borne by the superficial MCL (sMCL), posterior oblique ligament (POL), deep MCL (dMCL), and ACL were determined via the principle of superposition. Results: The POL bore about 50% of the load carried by the ACL in response to the combined torques at 5° and 15° of flexion. The POL bore load during the internal rotation component of the combined torques, while the sMCL carried load during the valgus and internal rotation phases of the simulated pivot. Load in the dMCL was always <10% of the ACL in response to combined valgus and internal rotation torques. Conclusion: The POL provides complementary load bearing to the ACL near extension in response to combined torques, which capture key components of the pivot-shift examination. The sMCL resists the valgus component of the maneuver alone, a loading pattern unique from those of the POL and ACL. The dMCL is not loaded during clinical tests of rotational knee stability in the ACL-competent knee. Clinical Relevance: Both the sMCL and POL work together with the ACL to resist combined moments, which form key components of the pivot-shift examination.